Voltage droop compensation based on resonant circuit for generalized high voltage solid-state Marx modulator - Canacsinh, Hiren (2017)
The purpose of this paper is to present and discuss the voltage droop compensation associated with long pulses generated by solid-state bipolar or unipolar high-voltage Marx modulators. In particular a novel design scheme for voltage droop compensation based on resonant circuit in solid-state bipolar (positive and/or negative pulses) high-voltage Marx generator, using off-the-shelf components, design and control, is described. The compensation consists in adding one auxiliary resonant stage to the existing Marx stages, without changing the modularity and topology of the circuit. The auxiliary compensation voltage is added to the output voltage to compensate the pulse voltage droop. Experimental results are presented for five stages Marx circuit, 10% voltage droop, using 1 kV pulse amplitude, 100 μs pulse width, 9.5 ms relaxation time and with 50 Hz pulse repetition rate.